The Strategies to Overcome the Stagflation in Moqavemati Economy Based On System Dynamics Approach - Aminiroaya, Mohammad; Mirzamohammadi, Saeed; Pishvaee, Mirsaman (International Journal of Engineering and Technology, 2018)
Moqavemati economy is an economic approach in which the economic structures and polices are designed so that in the most difficult conditions and most stresses, economic system act flexible and less fault accrued in progress way. Therefore, designing economical system based on the pattern of Moqavemati economy to solve economic problems and prevent their recurrence is essential. One of the problem that countries are faced with which is investigated in the study is stagflation that as an internal momentum caused removal of economic stability and the system shows inappropriate responds to the changes. Thus, the economic system design should be done so that the probability of this occurrence in different economic conditions reduce and drop to zero. In this study, a literature review on the problem of stagflation in local and foreign literature is done richly and completely. The study method applied in the paper, is system dynamics which has been used as managerial study method to analyze and model comprehensively and systematically Iran’s economy. The results derived from the study indicate the implementation of the five proposed policy annual reduction of 5% of oil revenues in the budget, an annual increase of 20% of non-oil exports, and adjusting the exchange rate on an annual basis by 15% and appropriate with expected inflation, an annual increase of 20% of construction projects and reducing the coefficient of increasing liquidity to the number 3, that all are based on the general policies of resistive economic causes the system to be stabilized and despite the different changes and shocks, it will be deviated from its main way when facing with stagflation and will continue to its way.